PENGARUH DISIPLIN PREVENTIF DAN LINGKUNGAN KERJA INTERNAL TERHADAP KINERJA KARYAWAN DI PTPN III SEI PUTIH DELI SERDANG - Amelia Febiyana Ginting; Abd. Rasyid Syamsuri (LPPM Universitas Labuhanbatu, 2020)
This study aims to analyze the effect of preventive discipline and internal work environment on employee performance at PTPN III Sei Putih Deli Serdang. The sampling technique is random sampling, namely the sample taken at random is 56 people. Methods of data collection using a questionnaire. The results of the simultaneous hypothesis test (F test) that the preventive discipline variable and the internal work environment have a positive and significant effect on employee performance. In the partial hypothesis test (t test) the variables of preventive discipline and the internal work environment have a positive and significant effect on employee performance. The results of the determination test obtained an R Square value of 0.778, meaning that the employee performance variable could be explained by 77.8% by the preventive discipline variable and the internal work environment while the remaining 22.2% was explained by other variables not included in this study.